2021
DOI: 10.3389/fnut.2021.747884
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, Anthocyanin-Rich Berries, and Cardiovascular Risks: Systematic Review and Meta-Analysis of 44 Randomized Controlled Trials and 15 Prospective Cohort Studies

Abstract: Objective: The associations between intake of anthocyanins and anthocyanin-rich berries and cardiovascular risks remained to be established. We aimed to quantitatively summarize the effects of purified anthocyanins and anthocyanin-rich berries on major surrogate markers of cardiovascular diseases (CVDs) and the longitudinal associations between dietary anthocyanins and CVD events.Methods: Meta-analysis of randomized controlled trials (RCTs) and prospective cohort studies.Results: We included 44 eligible RCTs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 54 publications
(80 reference statements)
3
44
0
Order By: Relevance
“…Berries are the most important dietary sources of anthocyanins (Xu et al 2021;Lin et al 2021). To date, very few studies have analyzed the impact that the altitude of production sites has on strawberry anthocyanins (Crespo et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Berries are the most important dietary sources of anthocyanins (Xu et al 2021;Lin et al 2021). To date, very few studies have analyzed the impact that the altitude of production sites has on strawberry anthocyanins (Crespo et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins reduced the risk of coronary heart disease and cardiovascular disease mortality but had no effect on myocardial infarctions, stroke or total cardiovascular disease [ 193 ]. A further analysis confirmed the decreased risk of cardiovascular disease with evidence that the protection could involve improved lipid profiles and decreased circulating pro-inflammatory cytokines [ 194 ]. An umbrella review showed a reduced risk of hypertension and improved markers of cardiometabolic disease but no effect on systolic or diastolic blood pressures [ 195 ].…”
Section: Therapeutic Actions Of Anthocyanins In Chronic Diseasesmentioning
confidence: 95%
“…By 2030, it is anticipated that every year, close to 28 million individuals would pass away from cardiovascular disease [3]. The high supply of anthocyanin is linked to a 17% less morbidity of coronary heart disease (CHD) [6]. Higher intake of anthocyanins reduces the risk of hypertension by 8-10% [7].…”
Section: Relationship Between Anthocyanin Intake and Cardiovascular M...mentioning
confidence: 99%
“…Additionally, the risk of myocardial infarction is decreased by up to 32%, greatly lowering the incidence rate of this condition [3]. A study shows that anthocyanin intake is associated with a 27% less danger of total CVDs, and anthocyanins have a more obvious protective effect on females [6].…”
Section: Relationship Between Anthocyanin Intake and Cardiovascular M...mentioning
confidence: 99%
See 1 more Smart Citation